REGULARITIES IN THE BEHAVIOR OF HYDROCARBON SYSTEMS OF OIL AND GAS POOLS - Buleiko V.M.; Voronov V.P.; Zakirov S.N.; Zakirov E.S.; Indrupskii I.M. (My University, 2007)
This paper considers the results of experimental investigations that confirm the important role of sorption in phase transformations in the productive collector and the distribution of hydrocarbon components between stationary and recoverable parts of the system. Sorption of high-boiling components of the bedded hydrocarbon mixture on walls of pore channels can change the composition of a filtering fluid. A decrease in the cross section of filtration channels can be accompanied by reduction of bed permeability and, as a consequence, hydrocarbon output. This is especially true of the methodology of laboratory experimentation.